The effects of screen time on dietary intake amongst adolescents in Kuala Selangor / Arfah Hana Zainal - Zainal, Arfah Hana (2016)
Healthy daily dietary intake of foods is important in adolescents' development in terms of learning, memory processing and also in general health. Food advertisement especially ones broadcasted by television are capable to influence food choices and intake of various unhealthy energy-dense nutrient-poor foods. Adolescents are one of the targeted market in most of the food advertised on television and other media mass. As a result, they are prone to be affected by the advertisement causing them to choose and incorporate unhealthy food choices into their daily diet. Meanwhile, times dedicated in screen time will highly influence the student's intake of food. Excessive allocation of daily screen time and poor intake of healthy foods may adversely affect the health and academic achievements of secondary school students. This study aims (i) to assess total screen time used, (ii) to identify the effects of screen time on food choices and dietary intake, and (iii) to identify the relation between screen time and BMI status all amongst secondary school students in Kuala Selangor. A total of 292 students (130 males and 162 females) aged twelve and fourteen years old from two rural schools located in Kuala Selangor district were involved in this cross sectional study. The instrument used was a questionnnaire titled "Kesan-kesan Masa Pengunaan Media Elektronik Terhadap Pengambilan Makanan Dalam Kalangan Remaja di Kuala Selangor". This questionnaire form consists of screen time questionnaire, dietary intake questionnaire and demographic and dietary intake during screen time questionnaire. The body mass index of students was categorised by using the World Health Organization BMI-for-age chart. The mean BMI and waist circumference of the students was 21.27 ± 5.10 and 72.52 ± 12.49 respectively. Result shows the mean score for total screen time of students during weekdays and weekend was 422.59 ± 256.14 and 654.06 ± 383.28 respectively. Majority of the students spent more than two hours per day on screen time, which exceeding the recommendation made by American Academy of Paediatric. From the analysis, it was found that total screen time during weekdays and weekend is not associated with BMI status of the students. In this study, food intake was classified into healthy eating pattern and unhealthy eating pattern. For daily dietary intake, a negative association was found between total screen time on weekdays and weekend with total dietary intake score. While for dietary intake during screen time, it was also found total screen time on weekdays and weekend is negatively associate with total dietary intake while screen time score. Thus, it can be concluded that the total screen time spent by students had no effects on their food choices and dietary intake. Further studies should incorporate broaden the study setting specifically at East Malaysia. Healthy daily dietary intake of foods is important in adolescents' development in terms of learning, memory processing and also in general health. Food advertisement especially ones broadcasted by television are capable to influence food choices and intake of various unhealthy energy-dense nutrient-poor foods. Adolescents are one of the targeted market in most of the food advertised on television and other media mass. As a result, they are prone to be affected by the advertisement causing them to choose and incorporate unhealthy food choices into their daily diet. Meanwhile, times dedicated in screen time will highly influence the student's intake of food. Excessive allocation of daily screen time and poor intake of healthy foods may adversely affect the health and academic achievements of secondary school students. This study aims (i) to assess total screen time used, (ii) to identify the effects of screen time on food choices and dietary intake, and (iii) to identify the relation between screen time and BMI status all amongst secondary school students in Kuala Selangor. A total of 292 students (130 males and 162 females) aged twelve and fourteen years old from two rural schools located in Kuala Selangor district were involved in this cross sectional study. The instrument used was a questionnnaire titled "Kesan-kesan Masa Pengunaan Media Elektronik Terhadap Pengambilan Makanan Dalam Kalangan Remaja di Kuala Selangor". This questionnaire form consists of screen time questionnaire, dietary intake questionnaire and demographic and dietary intake during screen time questionnaire. The body mass index of students was categorised by using the World Health Organization BMI-for-age chart. The mean BMI and waist circumference of the students was 21.27 ± 5.10 and 72.52 ± 12.49 respectively. Result shows the mean score for total screen time of students during weekdays and weekend was 422.59 ± 256.14 and 654.06 ± 383.28 respectively. Majority of the students spent more than two hours per day on screen time, which exceeding the recommendation made by American Academy of Paediatric. From the analysis, it was found that total screen time during weekdays and weekend is not associated with BMI status of the students. In this study, food intake was classified into healthy eating pattern and unhealthy eating pattern. For daily dietary intake, a negative association was found between total screen time on weekdays and weekend with total dietary intake score. While for dietary intake during screen time, it was also found total screen time on weekdays and weekend is negatively associate with total dietary intake while screen time score. Thus, it can be concluded that the total screen time spent by students had no effects on their food choices and dietary intake. Further studies should incorporate broaden the study setting specifically at East Malaysia.